Byggeklodser og blockbusters: Serialiseringspraksis på tværs af medier, materialer og modaliteter - Toft-Nielsen, Claus; Toft Nørgård, Rikke (Passage - Tidsskrift for litteratur og kritik, 2018)
Over the past seven decades millions of fingers have constructed their own worlds with LEGO bricks and controlled LEGO figures through digital, franchise-designed LEGO game worlds. This article explores the types of user interactions with these LEGO worlds as a specific form of ludic ‘seriality-in-use’ as the media invites its users to construct, interact with, and remix different storyworlds through LEGO. We explore this specific form of seriality – what we term ‘seriality-in-use’ – as serial forms that emerge from actual play instigations and manifestations and are expressed as practices of transmission, transformation, and transgression within and between specific media.